2017
DOI: 10.1016/j.jpba.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS determination of d-mannose in human serum as a potential cancer biomarker

Abstract: Several metabolites in human serum have been identified as potential cancer biomarkers for early detection. This study focuses on the LC–MS/MS method development and validation of D-mannose in human serum. Surrogate blank serum, coupled with stable isotope D-mannose-13C6, as internal standard, was used for generating standard curves ranging from 1 to 50 μg/mL. Separation was achieved by an Agilent 1200 series HPLC equipped with a SUPELCOGELTM Pb, 6% Crosslinked column with HPLC water as a mobile phase at flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
(17 reference statements)
3
14
1
Order By: Relevance
“…Chromatography of D-mannose in biological samples is complicated by the challenging separation from its endogenous epimers D-glucose and D-galactose, which often requires ad hoc strategies and specific materials [10]. In a recently published HPLC-MS-MS method, White et al [4] proposed the use of a Supelcogel Pb (Sigma-Aldrich, Saint Louis, MO, USA) column capable of separating sugars epimers by means of an ion exchange resin, which interacts with the analytes by both size exclusion and ligand exchange, the latter mechanism probably prevailing in the case of D-mannose.…”
Section: Methods Performancesmentioning
confidence: 99%
See 3 more Smart Citations
“…Chromatography of D-mannose in biological samples is complicated by the challenging separation from its endogenous epimers D-glucose and D-galactose, which often requires ad hoc strategies and specific materials [10]. In a recently published HPLC-MS-MS method, White et al [4] proposed the use of a Supelcogel Pb (Sigma-Aldrich, Saint Louis, MO, USA) column capable of separating sugars epimers by means of an ion exchange resin, which interacts with the analytes by both size exclusion and ligand exchange, the latter mechanism probably prevailing in the case of D-mannose.…”
Section: Methods Performancesmentioning
confidence: 99%
“…In particular, biochemical and genetic data have shown that genes involved in the O-mannose glycosylation pathway may cause forms of congenital muscular dystrophy in humans [2]. Moreover, mannose has been implicated in cancer metabolism and is considered to be a reliable biomarker for esophageal adenocarcinoma (EAC) [3,4]. Moreover, serum concentrations of D-mannose have been reported to be higher in metastatic breast cancer patients than in early-stage breast cancer [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although such studies offer effective information for the early diagnosis and prognosis of AD and also provide constructive suggestions for AD pathogenesis elucidation, due to the intrinsic particularity of protein macromolecules, their dissemination in clinical detection for AD faces many challenges, including determining the preservation and testing conditions, diagnosis interval, and cost. Peripheral blood metabolic biomarkers have gained more attention with the development of HPLC-MS technology, our increasing understanding of the metabolic pathways of small molecules, and the gradual perfection of small molecule databases [20-22]. In the present study, metabolites in the peripheral sera of patients with AD were examined by HPLC-MS and compared with corresponding metabolite levels in healthy subjects and hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%